Methods for measuring the cost of the most affordable nutritionally adequate diet in a country - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The research has been extensively cited. Donors have recognized how the methodology can be used to guide their own strategies and approaches. Efforts are now focused on equipping governments and development agencies with accurate, updated metrics to monitor diet costs and affordability to inform agricultural and food systems interventions.